Azharite Muhammadiyah: Ambivalence and Reinterpretation of Muhammadiyah Identity - Fahmi Wira Angkasa (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2022)
The existence of Al-Azhar in Cairo has produced many alumni who carry the message of wasatiyah Islam to all elements of society, including the Muhammadiyah muslim organization. Muhammadiyah as a reformist Islamic institution is often claimed has similarity with Salafi. Then Muhammadiyah is considered to have a different manhaj from Al-Azhar, which in terms of teaching curriculum and movement has many conflicts with Salafi. This fact makes Muhammadiyah cadres who study at Al-Azhar experience ambivalence of identity. This study analyses how Azharite Muhammadiyah's role in the contribution of thoughts against Salafi who still have influence in Muhammadiyah's proselytization movement. This paper uses qualitative methodology, by interviewing some Muhammadiyah cadres, alumni of Al-Azhar who are affiliated with Muhammadiyah. In addition, I conducted digital observations to find data on disputes and debates that occurred between the Muhammadiyah Salafi (Musa) and those who were resistant to their thoughts. I also observe the movements that have been carried out by Azharite Muhammadiyah in fighting for the identity of Muhammadiyah, that Muhammadiyah should not be identified as Salafi. I found that Azharite has been success to campaign that Muhammadiyah is different with Salafi. Lack understanding of members to the Muhammadiyah doctrine is the main factor of the Salafism doctrine development among Muhammadiyah. This paper is expected to reevaluating the Muhammadiyah fatwa which is applied in Muhammadiyah mosques and madrasa, and to put HPT as the primary reference of teaching.